2016
DOI: 10.4315/0362-028x.jfp-15-336
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes in Retail Delicatessens: An Interagency Risk Assessment—Risk Mitigations

Abstract: Cross-contamination, improper holding temperatures, and insufficient sanitary practices are known retail practices that may lead to product contamination and growth of Listeria monocytogenes. However, the relative importance of control options to mitigate the risk of invasive listeriosis from ready-to-eat (RTE) products sliced or prepared at retail is not well understood. This study illustrates the utility of a quantitative risk assessment model described in a first article of this series (Pouillot, R., D. Gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Following the 2003 FDA-FSIS risk assessment and several other product-specific risk assessments to evaluate the impact of interventions [5,6,36], FDA and FSIS issued regulations and guidance on risk-based Listeria control [1,[37][38][39][40][41]. The food industry, working with academia, also developed guidance for risk-based Listeria control and made changes to industry practices [42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Following the 2003 FDA-FSIS risk assessment and several other product-specific risk assessments to evaluate the impact of interventions [5,6,36], FDA and FSIS issued regulations and guidance on risk-based Listeria control [1,[37][38][39][40][41]. The food industry, working with academia, also developed guidance for risk-based Listeria control and made changes to industry practices [42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…The first is linked to cross-contamination at retail level. It has been recently shown that cross-contamination at retail is of major importance for L. monocytogenes (Pouillot et al, 2015;Gallagher et al, 2016). Yet cross-contamination probably concerns products of the same food category, e.g.…”
Section: Consistency Of Clusters Establishedmentioning
confidence: 99%
“…Extensive testing and observations of worker behavior showed that these deli meats tended not to contain added inhibitors; resident L. monocytogenes were present in niches in equipment and spread through cross-contamination from food contact and non-food contact surfaces; and there was lack of adequate sanitation; inadequate temperature control; and inappropriate glove/hand issues. This information was used to create a "virtual deli" model and to generate six baseline situations and 22 scenarios by the U.S. Department of Health and Human Services; Center for Food Safety and Applied Nutrition, Food and Drug Administration and the U.S. Department of Agriculture Food Safety and Inspection Service [24][25][26]. Overall, the virtual deli model indicated that the greatest risk was from contamination present in an incoming chub of a product that permitted growth of Listeria.…”
mentioning
confidence: 99%